ANALISIS ETIKA PROFESI TUTOR PENDIDIKAN DALAM MEMBENTUK PROFIL LULUSAN SOSIOEDUPRENEUR - Riyan Saputra; Holva Lovana Siregar (SINERGI : Jurnal Riset Ilmiah, 2026)
This study was motivated by the importance of professional ethics in the management of non-formal educational institutions, particularly Community Learning Centers (PKBM) such as SKB Kota Bogor. Community education tutors play a strategic role in determining the quality of vocational training, thus requiring a professional attitude based on moral values and ethics to shape the profile of socio-entrepreneurial graduates. This study aims to determine the application of professional ethics by barista training tutors at SKB Kota Bogor in carrying out their duties and responsibilities. The research method used is qualitative with observation and in-depth interview techniques. The main informant in this study was Mr. Haidar as a barista training tutor. The results showed that the application of professional ethics was reflected in honest, fair, responsible, transparent, and professional attitudes in teaching skills, managing participants, assessing practices, and relating to the community. The tutor also emphasized the balance between personal interests and the formation of innovative socio-edupreneur graduates. The conclusion of this study shows that professional ethics not only serve as a code of conduct but also become an important factor in building community trust and creating a healthy training environment for graduates with integrity.